Distribution process of Navana LPG, challenges of distribution process and upcoming future prospects of LPG in the context of Bangladesh - Hossain, Syeda Rawnak (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.